Analisis Fatwa DSN MUI No 108 Tahun 2016 Tentang Pariwisata Halal Perspektif Mashlahah Mursalah - Desi Wulandari, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The main sources of Islamic law are the Al-Qur'an and As-Sunnah to determine issues that arise in people's lives. However, as time goes by, new legal issues arise which sometimes cannot be resolved with the main sources of law, so it is necessary to develop new methodologies to deal with these problems, but not to neglect the objectives of these main sources, some of the fuqaha agree to offer the mashlahah mursalah method. as an effort to resolve contemporary legal issues that arise at the time recently. In DSN-MUI No. 108 of 2016 concerning halal tourism can be understood that this fatwa includes Al-Maslahah al-'Ammah, namely the general benefit that concerns the interests of many people. The general good does not mean for the benefit of everyone, but it can take the form of the interests of the majority of the people or most of the people. And from the other side it includes maslahah dharuriyat because it is guarded from two sides: first, its realization and embodiment, and secondly, maintaining its sustainability. In this case, tourists in doing tours will comply with sharia guidelines. Keywords: DSN MUI Fatwa No.108 of 2016, Halal Tourism, Mashlahah Mursalah